Root detection by resistivity imaging and physiological activity with the dead-end trench on three clones of cocoa (Theobroma cacao) - Canggih Nailil Maghfiroh Nailil; EKA TARWACA SUSILA PUTRA; ENDANG SRI DEWI HS (Society for Indonesian Biodiversity, 2020)
Abstract. Maghfiroh CN, Putra ETS, Dewi HSES. 2020. Root detection by resistivity imaging and physiological activity with the dead-end trench on three clones of cocoa (Theobroma cacao). Biodiversitas 21: 2794-2803. Indonesia is one of the largest cocoa production countries in Southeast Asia, but has low average productivity (982 kg/ha) based on Indonesian Plantation Statistics (2017). Productivity increase effort by giving dead-end trenches that applied to collect organic material, accommodate surface runoff sediments, prevent erosion, and maintain nutrient availability. Dead-end trench had an impact on root cutting and improve rooting. Clone is very influential on cocoa (Theobroma cacao L.) yield. The superior clones recommended are clones RCC-70, RCC-71, and KKM-22, which have high productivity and are resistant to pests and diseases. The objectives of this research were (i) to detect the presence of roots by resistivity imaging (ii) to study the effects of dead-end trench application on physiological activities of cocoa leaves and yields of three clones (RCC-70, RCC-71, and KKM-22); (iii) to determine which cocoa clone (s) performed a significant yield increase with the application of dead-end trench. Research was conducted in August 2018-April 2019 at PT. Pagilaran cocoa plantation in North Segayung Production Unit, subdistrict Tulis, Batang, Central Java. The experiment was arranged in a randomized complete design with two factors and three blocks as replications. The first factor was dead-end trench application (with or without dead-end trench application) and the second factor was cocoa clones (RCC-70, RCC-71, and KKM-22). This study showed that dead-end trench applications affected plant roots based on the interpretation results of geoelectric-resistivity measurements. Dead-end trench application significantly affected chlorophyll a, stomatal conductance, transpiration, and H2O leaf content. Dead-end trench application has no significant effect on the content of chlorophyll b, total chlorophyll content, nitrate reductase activity, stomatal density, CO2 leaf content, and photosynthesis rate.